Análisis de los programas de entrenamiento físico y rehabilitación en pacientes con enfermedad renal crónica. - Logroño Álvarez, Jhonnatan Fabricio (2024)
Chronic kidney disease (CKD), also known as chronic renal failure, describes the gradual loss of kidney function. When CKD reaches an advanced stage, dangerous levels of fluids, electrolytes, and waste can accumulate in the body. Objective: To analyze the evidence from previous studies on physical training and rehabilitation programs. Material and Methods: A systematic literature review was conducted. Search strategies followed PRISMA guidelines. The search was conducted in Spanish and English in Medline/PubMed, Web of Science, and Scopus. The PEDro scale was used to assess the methodological quality of the articles. Results: The systematic review was finally carried out with 20 original studies conducted in different countries. Nine articles coincide on the exercises and techniques used in various physical training programs for individuals with CKD. The studies propose alternatives such as aerobic exercises and progressive resistance exercises. Eleven articles were found in Latin America and Europe. Conclusions: The best alternatives for physical training and rehabilitation programs in patients with CKD are programs that include aerobic exercises and progressive resistance exercises.